Analisis Kesulitan Mahasiswa Santri Fakultas Tarbiyah Universitas Ibrahimy Sukorejo Situbondo dalam Menyusun dan Menyelesaikan Tugas Akhir Skripsi (TAS) pada Tahun 2023 - Maswar Maswar (Jurnal Multidisiplin Ibrahimy, 2024)
This research reveals the difficulties Santri students face at the Tarbiyah Faculty of UNIB Situbondo in compiling and completing their final thesis assignment (TAS) in 2023. The research method used combines two approaches, descriptive quantitative and qualitative. The descriptive approach is the preparation and presentation of data into images or graphs. Meanwhile, the quantitative approach analyzes quantitative data obtained through questionnaire instruments regarding the average percentage of difficulties faced by Islamic boarding school students. Quantitative data was analyzed using descriptive and inferential statistics with the help of the Excel/SPSS 23 program. The qualitative approach was to carry out an analysis of qualitative data obtained through interview instruments. The population in this study was 256 Tarbiyah Faculty students who graduated in 2022-2023. Meanwhile, the samples taken as research objects/subjects were 64 students. The sample size used was 25% of the total population. The results of the research show that three indications are very dominant faced by students, namely: 1) students have difficulty in determining statistical formulas that suit the data (percentage 82.26%), 2) students have difficulty in using statistical program applications such as SPSS, Eviews, Smart PLS and others are often used in processing/analyzing research data (percentage 91.94%), and 3) students feel anxious while waiting for the thesis exam, worried or afraid when facing the thesis exam (percentage 87.10%).